2020
DOI: 10.1021/acs.est.9b07564
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Decomposition of New Iodinated Halobenzoquinones during Chloramination in Drinking Water

Abstract: Previously four chlorinated and brominated halobenzoquinones were reported as new disinfection byproducts (DBPs) in drinking water, which have drawn great concern due to their high toxicity. In this study, three new iodinated halobenzoquinones, including 2-chloro-6-iodo-1,4-benzoquinone (2,6-CIBQ), 2-bromo-6-iodo-1,4-benzoquinone (2,6-BIBQ), and 2,6diiodo-1,4-benzoquinone (2,6-DIBQ), were detected and identified in drinking water for the first time. Their cytotoxicity was evaluated, and their formation under v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…The isomer of higher polarity would easily enter into the cell and induce higher cytotoxicity. Similar results were also reported for the cytotoxicity of halobenzoquinones in CHO-K1 cells and HepG2 cells. , Third, the lowest cytotoxic concentration (induced a statistically significant reduction as compared to the negative control) of five HQCs and 2,6-DCBQ was calculated by the Holm-Sidak method with the power (1-β) ≥ 0.8 at α = 0.05 after a significant F value was obtained ( P < 0.05). The lowest cytotoxic concentration of six analytes was 2,6-DCQC (20 μM), 2,6-DCBQ (160 μM), 2-CQC (15 μM), 3-CQC (80 μM), 2,6-DCMQC (120 μM), and 2,6-DBQC (60 μM).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The isomer of higher polarity would easily enter into the cell and induce higher cytotoxicity. Similar results were also reported for the cytotoxicity of halobenzoquinones in CHO-K1 cells and HepG2 cells. , Third, the lowest cytotoxic concentration (induced a statistically significant reduction as compared to the negative control) of five HQCs and 2,6-DCBQ was calculated by the Holm-Sidak method with the power (1-β) ≥ 0.8 at α = 0.05 after a significant F value was obtained ( P < 0.05). The lowest cytotoxic concentration of six analytes was 2,6-DCQC (20 μM), 2,6-DCBQ (160 μM), 2-CQC (15 μM), 3-CQC (80 μM), 2,6-DCMQC (120 μM), and 2,6-DBQC (60 μM).…”
Section: Resultssupporting
confidence: 76%
“…Similar results were also reported for the cytotoxicity of halobenzoquinones in CHO-K1 cells and HepG2 cells. 35,50 Third, the lowest cytotoxic concentration (induced a statistically significant reduction as compared to the negative control) of five HQCs and 2,6-DCBQ was calculated by the Holm-Sidak method with the power (1-β) ≥ 0. S6 and S7.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three Cl-aromatic DBPs, including 3,5-DCl-2-HBA (19.7 ng/L), 3,5-DCl-4-HB (17.7 ng/L), and 2,4,6-TClP (15.1 ng/L), were the dominant species among the nine aromatic halogenated DBPs and accounted for 70%, which was much higher than those of the measured Br-aromatic (27%) and I-aromatic DBPs (3%). Increasing the chlorine dose for emergency disinfection can accelerate the formation and decomposition of aromatic (non)­halogenated DBPs and thus increase the formation of aliphatic DBPs, including THMs, HAAs, and other DBPs, in disinfected waters. This might account for the low detection frequencies and concentrations of the nine aromatic DBPs measured in Wuhan and Beijing. For all tap water samples, NDMA (22.9 ng/L), NMEA (13.8 ng/L), and NDEA (8.9 ng/L) were the three most dominant species and accounted for 69% among nine NAs.…”
Section: Resultsmentioning
confidence: 99%
“…Disinfection byproducts (DBPs) are inevitably generated during drinking water disinfection by the reaction of disinfectant with organics and halides . Numerous epidemiologic and metabolomic observations have identified associations between the long-term consumption of chlorinated drinking water and adverse health risks such as abnormal pregnancy outcomes, bladder cancer, and cardiac birth defects. Many researchers have aimed to identify the DBP that may act as toxicity drivers in drinking water. Since chloroform was first reported in chlorinated drinking water in the 1970s, more than 800 DBPs have been identified and confirmed. Trihalomethanes (THMs) and haloacetic acids (HAAs), carbonaceous DBPs (C-DBPs), are currently regulated by the United States Environmental Potency Agency, but no evidence has shown that they are drivers of elevated bladder cancer risk. , Nitrogenous DBPs (N-DBPs) are reported to be more toxic than C-DBPs. , Recently, a number of aromatic DBPs have been identified in drinking waters. Aromatic DBPs are of concern due to their high toxicity, often 3 to 4 orders of magnitude higher than regulated DBPs. , Furthermore, it has been reported that the metabolic rate of aromatic nitrogenous groups in heterotrophic organisms was significantly lower than that of non-nitrogenous aromatic groups, indicating they are slowly metabolized by humans. , In other words, aromatic N-DBPs in drinking water may be important components of the overall toxicity. Recently, chlorophenylacetonitriles (CPANs), an emerging class of aromatic N-DBPs, have been identified in drinking water. , Chronic cytotoxicity tests based on Chinese hamster ovarian (CHO) cells have shown that the CPANs are 2 to 3 orders of magnitude more cytotoxic than regulated THMs and HAAs.…”
Section: Introductionmentioning
confidence: 99%